CD28 family of receptors inter-connect in the regulation of T-cells - Krueger, Janna (Receptors Clin Investig, 2017)
T-cell activation is mediated by a combination of signals from the antigen receptor (TCR) and co-receptors such as CD28, cytotoxic T-lymphocyte antigen-4 (CTLA-4), programmed cell death antigen 1 (PD-1), CD28H and others. Each is a member of the CD28 receptor gene family. CD28 sends positive signals that promote T-cell responses, while CTLA-4 and PD-1 limit responses. It is the balance between these positive and negative signals that determines the amplitude and level of T-cell responses. The regulatory role of other family members is also becoming the focus of increasing interest. The function of certain CD28 family members such as CTLA-4 and PD-1 is dependent the expression of CD28. Together, these findings have important implications in generation of immune responses and the application of anti-receptor blocking reagents in immunotherapy.